Pengabdian pada masyarakat dalam upaya promotif berupa peningkatan kemampuan remaja putri tentang program pendewasaan usia perkawinan (PUP) di Desa Banguntapan Bantul - Nur Djanah; Monica Muaslimah; Restu Wulan Ayuningtyas (Jurnal Kesehatan Pengabdian Masyarakat (JKPM), 2020)
The government has proclaimed the marriage Age maturity Program (PUP) since 2006. PUP is an effort to increase the age of the first marriage so that it reaches the minimum age at the time of the marriage, which is 20 years old for women and 25 years for men. PUP is not just a delay to a certain age but also to try to have a first pregnancy occurs at a fairly mature age. With the PUP expected the youth have an understanding and awareness in planning the family, considering various aspects relating to family life, physical, mental, emotional, educational, social, economic and determining the number and distance of birth. Considering the various aspects related. Through the PUP program, it is expected to improve the first married age (UKP) and eventually also to reduce Total Fertility Rate. The PUP program is conducted through a family life preparation program for adolescents (PKBR) in the activities of youth Counseling and Information Center (PIK-R) in schools and corals. The activities of public devotion conducted in PPG Al-Karima village Banguntapan Bantul related to the knowledge and understanding of the marriage age maturity Program for young women is the implementation of research in 2016 conducted by Muslihatun and Djanah on the maturity Program of marriage and age plan to marry teenage princess in SMK N 2 Sewon Bantul D. I Yogyakarta. The outdoor Target of this community service program is the increase and increase in adolescent knowledge of the concept of adulthood, adolescent reproductive rights, adulthood in adolescent marriage and the youth mating program. Methods spoken by lectures, video views and FAQs. Participants were enthusiastic to join the activity. The obstacles are the background of the understanding of the maturity of the marital age that tends to vary from each participant.